Governança e comunidade local : a experiência do Museu do Mangue - Silva, Eliene Oliveira da (2020)
The research project is based on the governance performed at the Mangrove’s Museum, in the Coroa do Meio district, in the capital of Sergipe. The management actions that the municipality of Aracaju has adopted in light of the current environmental legislation are aimed at conservation, mainly in mangrove areas. The idea of governance seeks to promote political pluralism, in which the local community is involved in the construction of public policies, whose social capital is a determining factor in environmental governance. Environmental Education, as an interdisciplinary action, contributes to the empowerment of the community with the environment, involving the subjects in planning in a social, economic and environmental bias. The general objective is to analyze the governance employed at the mangrove’s museum and the participation of the local community in decision-making. and the specific objectives are: to identify the actors involved in the historical constitution of the mangrove’s museum; describe the elements that triggered the creation of the mangrove museum; know the environmental education actions developed at the mangrove’s museum; and, to evaluate the public policies of socio-environmental development, in the construction and functionality of the mangrove museum. The general objective is to analyze the environmental governance and its articulation with the local community, in the decision making regarding the Mangrove’s Museum, in the Coroa do Meio district. The research is classified as qualitative with an exploratory approach, within the phenomenological method, with an instrument for data collection, document analysis, systematic observation, semi structured interviews with managers, institutions, ONGs, community representatives and use of photographic records. The interviews were analyzed using the Iramuteq software, generating a maximum similarity tree. It can be concluded that effective citizen participation in the construction of public policies from the perspective of the environmental governance of the Mangrove’s Museum, modifies the impacts on the mangrove, defining limits, adding rights and duties to all actors involved, providing even greater quality collective life.